Symposium on administrative reform in the Pacific Rim areas (Special feature)
The articles in this symposium reflect the successes and failures of reform in the Pacific Rim Countries. Gerald Caiden discusses the administrative changes in Australia and New Zealand that have greatly altered the values and behaviour of public officials in terms of improving the public-sector performance and transforming `sheltered bureaucratism to open managerialism'. King Chow examines the logical consistency and rational comprehensiveness of the proposed reform of the civil service system in China and the political context in which reform measures are to be undertaken. Chung-Kil Chung and Jong S. Jun address the irony of Cutback reform in korea, that is ambitious reform goals and the difficulty of ac
Keywords: Administrative Reorganisation